2016
DOI: 10.1007/s00726-016-2214-3
|View full text |Cite
|
Sign up to set email alerts
|

Traf2- and Nck-interacting kinase (TNIK) is involved in the anti-cancer mechanism of dovitinib in human multiple myeloma IM-9 cells

Abstract: Traf2- and Nck-interacting kinase (TNIK) is a member of the germinal center kinase family. TNIK was first identified as a kinase that is involved in regulating cytoskeletal organization in many types of cells, and it was recently proposed as a novel therapeutic target in several types of human cancers. Although previous studies suggest that TNIK plays a pivotal role in cancer cell survival and prognosis, its function in hematological cancer cell survival has not been investigated. Here we investigated the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…TNIK is highly expressed in MM cells compared to normal peripheral blood mononuclear cells (PBMCs), and inhibition of TNIK expression by siRNA induces cell death. KY-05009 and dovitinib have a high affinity for the ATP binding site in TNIK and inhibit the protein expression of TNIK and transcriptional activity of Wnt target genes [11, 12]. Through these our recent reports, we confirmed that TNIK can be a potential target for inducing apoptosis activity of KY-05009 and dovitinib in cancer cells.…”
Section: Introductionsupporting
confidence: 59%
See 4 more Smart Citations
“…TNIK is highly expressed in MM cells compared to normal peripheral blood mononuclear cells (PBMCs), and inhibition of TNIK expression by siRNA induces cell death. KY-05009 and dovitinib have a high affinity for the ATP binding site in TNIK and inhibit the protein expression of TNIK and transcriptional activity of Wnt target genes [11, 12]. Through these our recent reports, we confirmed that TNIK can be a potential target for inducing apoptosis activity of KY-05009 and dovitinib in cancer cells.…”
Section: Introductionsupporting
confidence: 59%
“…In the last 10 years, TNIK has been reported as a novel therapeutic target in several types of cancers. In many studies, the expression of TNIK has been shown to be involved in the survival of human cancer cells, including colorectal, gastric, liver, and hematological cancer [611]. Wnt signaling is mediated by TNIK through interactions with β-catenin and following phosphorylation of T-cell factor (TCF) 4 at serine 154 in the nucleus.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations